2021
DOI: 10.1007/s10584-021-03169-y
|View full text |Cite
|
Sign up to set email alerts
|

Divergent, plausible, and relevant climate futures for near- and long-term resource planning

Abstract: Scenario planning has emerged as a widely used planning process for resource management in situations of consequential, irreducible uncertainty. Because it explicitly incorporates uncertainty, scenario planning is regularly employed in climate change adaptation. An early and essential step in developing scenarios is identifying “climate futures”—descriptions of the physical attributes of plausible future climates that could occur at a specific place and time. Divergent climate futures that describe the broades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…We plotted the change in annual average temperature and annual average precipitation in the 2041-2071 projections relative to the 1961-1990 historical normals for the 31 climate futures. Similar to Lawrence et al [50], we found groupings of climate futures were based on AOGCMs and not emission scenarios (Figure 3). We used the plot to identify the warm and the wet (MPI-ESM1-2-HR, SSP2-4.5) and the warmest and the wettest (UKESM1-0-LL, SSP5-8.5) projection.…”
Section: Biome Plotssupporting
confidence: 86%
“…We plotted the change in annual average temperature and annual average precipitation in the 2041-2071 projections relative to the 1961-1990 historical normals for the 31 climate futures. Similar to Lawrence et al [50], we found groupings of climate futures were based on AOGCMs and not emission scenarios (Figure 3). We used the plot to identify the warm and the wet (MPI-ESM1-2-HR, SSP2-4.5) and the warmest and the wettest (UKESM1-0-LL, SSP5-8.5) projection.…”
Section: Biome Plotssupporting
confidence: 86%
“…The information within the CCVD portfolios is also valuable for use in decision support, for example, via scenario planning [37,38] whereby manager-researcher teams evaluate a range of future scenarios in order to understand risks and prioritize management actions in the face of uncertainty [39,40]. Scenario planning techniques are increasingly being used by managers as a climate change adaptation tool when uncertainty is high and when multiple competing climate models predict a set of plausible, but divergent, possible futures [41,42]. Given the high uncertainty in future climate, especially rainfall projections in Hawai'i where small land area makes predictions difficult [19,20,43], the PDKE CCVD portfolios add critical information as raw material to support important conservation and restoration planning discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Projected rates of warming are highly variable at regional and local scales. Thirteen CMIP 5 general circulation models (GCMs) within each RCP were selected from the MACA dataset such that they bracketed the range of projected future changes in temperature and precipitation (Lawrence et al, 2021; Rupp et al, 2013). The 13 GCMs were CanESM2, NorESM1‐M, BNU‐ESM, MRI‐CGCM3, CNRM‐CM5, CSIRO‐Mk3‐6‐0, MIROC‐ESM‐CHEM, MIROC5, GFDL‐ESM2G, CCSM4, HadGEM2‐CC365, inmcm4, and IPSL‐CM5A‐LR.…”
Section: Methodsmentioning
confidence: 99%